The cAMP responsive element-binding (CREB)-1 gene increases risk of major psychiatric disorders. Issue 9 (September 2018) - Xiao, X; Zhang, C; Grigoroiu-Serbanescu, M; Wang, L; Li, L; Zhou, D; Yuan, T-F; Wang, C; Chang, H; Wu, Y; Li, Y; Wu, D-D; et al.
Abstract Bipolar disorder (BPD), schizophrenia (SCZ) and unipolar major depressive disorder (MDD) are primary psychiatric disorders sharing substantial genetic risk factors. We previously reported that two single-nucleotide polymorphisms (SNPs) rs2709370 and rs6785 in the cAMP responsive element-binding (CREB)-1 gene (CREB1 ) were associated with the risk of BPD and abnormal hippocampal function in populations of European ancestry. In the present study, we further expanded our analyses of rs2709370 and rs6785 in multiple BPD, SCZ and MDD data sets, including the published Psychiatric Genomics Consortium (PGC) genome-wide association study, the samples used in our previousCREB1 study, and six additional cohorts (three new BPD samples, two new SCZ samples and one new MDD sample). Although the associations of bothCREB1 SNPs with each illness were not replicated in the new cohorts (BPD analysis in 871 cases and 1089 controls (rs2709370, P =0.0611; rs6785, P =0.0544); SCZ analysis in 1273 cases and 1072 controls (rs2709370, P =0.230; rs6785, P =0.661); and MDD analysis in 129 cases and 100 controls (rs2709370, P =0.114; rs6785, P =0.188)), an overall meta-analysis of all included samples suggested that both SNPs were significantly associated with increased risk of BPD (11 105 cases and 51 331 controls; rs2709370, P =2.33 × 10−4 ; rs6785, P =6.33 × 10−5 ), SCZ (34 913 cases and 44 528 controls; rs2709370, P =3.96 × 10−5 ; rs6785, P =2.44 × 10−5 ) and MDD (9369 cases and 9619 controls; rs2709370, P =0.0144; rs6785, P =0.0314), with the same direction of allelic effects across diagnostic categories. We then examined the impact of diagnostic status onCREB1 mRNA expression using data obtained from independent brain tissue samples, and observed that the mRNA expression ofCREB1 was significantly downregulated in psychiatric patients compared with healthy controls. The protein–protein interaction analyses showed that the protein encoded byCREB1 directly interacted with several risk genes of psychiatric disorders identified by GWAS. In conclusion, the current study suggests thatCREB1 might be a common risk gene for major psychiatric disorders, and further investigations are necessary.